Prohibitions in Phonetic Performance in the Arabic Language - Hassan El-Malkh; Suha Na’ja (My University, 2014)
This research has aimed using a descriptive and analytical approach to elucidate the phonetic prohibitions phenomena that the Arabic Language prevents from performing on the operative level. It has come clear that the Arabic Language takes into account the phonetic identity of each of its phonemes that are accepted on the Formal level, and fortifies the linguistic functions with specific significances in the light of the linguistic phoneme essence, it also preserves the performance habits in pronunciation when the conjunction occurs of two or more phones to form an Arabic or Arabized word. The research has found that the structural performance of the linguistic functions is a phonetic pyramid consolidating in its functional input with the phonetic validity of each single phoneme or the phonemes combined in a word, and to maintain the right phonetic sequence between words in terms of pronunciation, structure, connection, separation, and stopping in the light of the correct bilateral phonetic performance and the semantic significance entrusted in it, with restrictions imposed on going out of the correct phonetic positions such as the poetic necessities that are well recognized in the Arabic poetry. The research has confirmed that the phonetic identity is a key in the preservation of the Arabic Language, tracing the mores of the Arabs in their language according to the formal level which is set in grammar and morphology.

هدفَ البحثُ بمنهجٍ وصفيٍّ تحليليّ إلى استجلاء ظاهرة المحظورات التي تمنع العربيّةُ أداءَها في المستوى الصوتيّ منها عندَ التلفّظ السليم الصحيح قراءةً وتَداولاً، فتبيَّنَ أنَّها تقوم على مراعاة الهُوية الصوتيّة لكلّ صوتٍ من أصوات العربيّة المقبولة في المستوى الفصيح العامّ منها، ومُراعاة الانسجام الصوتيّ الصحيح نطقاً ودلالة ومُحافظة على العادات الأدائيّة في النطق عندَ اقتران صوتين فأكثر لتكوين كلمة عربيّة أو مُعرَّبة في العربيّة، ووصل البحثُ إلى أنَّ الأداء التركيبيّ للكلمات هَرَمٌ صوتيٌّ يتماسَكُ في مُدخلاته من الكلمات بالصحّة الصوتيّة للصوتِ المفرد، أو الأصوات المؤتلفة في كلمةٍ، ثمّ توخّي التتابع الصوتيّ السليم بين الكلمات نطقاً ونحواً ووصلاً وفصلاً ووقفاً في ضوء ثنائيّة جَبريّة بين الأداء الصوتيّ الصحيح والغاية الدلاليّة المنوطة به مع تقييدِ الخروج عن المواضعات الصوتيّة الصحيحة بحالات الضرورة الشعريّة المتعارف عليها في الشعر العربيّ، وأكَّدَ البحثُ أنَّ ديمومةَ العربيّة بدَيمومةِ المحافظة على هُويتها الصوتيّة، لكي تكون بحقٍّ اقتفاءً لسَنَن العربِ في كلامها حسبَ المستوى الفصيح المقَعَّد في النحو والصرف.
المحظورات الصوتيّة الأدائيّة في العربيّة